Internationalization Process and Business Strategies: A Case Study of Malaysia's Growth Multinational Company - Pensonic Holdings Berhad - Oon, Kam Hoe (2010)
In the past two decades, internationalization process of firms has been the topic of much debate and study by the scholars or researchers in the field of international business. Yet, most studies are focusing on the international expansion of MNCs from the western perspective and little attention has been given in examining and analyzing the internationalization process of the developing/emerging economies multinational enterprises (MNEs). In this study, the internationalization process and the business strategies of emerging firm has been studied and examined empirically with the application of international business theories. The purpose of this study is to develop a Malaysia perspective of internationalization and business strategies which contribute to the development of Malaysia SMEs in international context. In order to develop a holistic overview of internationalization process and business strategies in Malaysia perspective, a potential Malaysia's MNEs - Pensonic Holdings Berhad has been selected and used to be the foundation of this study. Basically, there are three specific international business theories that are adopted to review the internationalization process of Pensonic Holdings Berhad. Practically, those theories are Johanson & Mattson internationalization model (interactive network approach), international springboard perspective, and international new venture theory. Subsequently, three propositions have been developed to test the propensity of Pensonic to internationalize and its business strategies towards internationalization process. As an overview of the findings, there are three interlink influential relationships implied on the propensity of SMEs to expand abroad, the SME's actions and strategies, and the internationalization process. Thus, the result shows that the propensity of SME to internationalize is the foundation to leads for successful internationalization process. Based on the results, this study recommended that Malaysia's SMEs should undertake the advantages and opportunities available in the Malaysia's business environment such as government supports and assistances to expand abroad successfully.